Atividade da enzima redutase do nitrato e teores de prolina livre em raízes de cana-de-açúcar sob os estresses hídrico e ácido no solo - de Lima Rhein, Andressa Freitas [UNESP]; Mathias dos Santos, Durvalina Maria [UNESP]; Carlin, Samira Domingues (Universidade Estadual de Londrina (UEL), 2011)
The aim of this work was evaluate the physiological indicators of association between water deficiency and soil acidity, by determining the nitrate reductase activity, the levels of free proline and initial growth of the root system of seedlings of sugarcane cv. IAC91-5155. After 30 days, the seedlings were transferred to plastic pots with 12 dm3 of dystrophic alic Red Latosol (Oxisol) and submitted to association of three treatments of water availability: no stress (70%), moderate stress (55%) and severe stress (40%), in according with field capacity and three acidity treatments: no stress (55%), moderate stress (33%) and severe stress (23%), considering the base saturation. The experimental design was that of random blocks under factorial scheme of 3x3, with four replicates. After 60 days under the stress association, the levels of free proline, the nitrate reductase activity and the growth of the sugarcane roots system were evaluated in seedlings of sugarcane. The nitrate reductase enzyme activity can be considered a physiological indicator of the effect of the association of acid and water stress in moderate conditions in soil, while the free proline can be considered physiological indicator to both stress in severe conditions. Water deficiency increasing reduced growth of sugarcane roots.
Nitrate reductase enzyme activity and free proline contents in sugarcane roots under water and acid stress in soil
Keywords: Abiotics stress; nitrogen; osmoprotector; root system; Saccharum spp.